A case study on the efficiency of E-recruitment as a new approach in selecting potential candidate at Technology Park Malaysia Corporation Sdn. Bhd. / Nur Hidayah Hassan - Hassan, Nur Hidayah (Faculty of Business and Management, 2011)
This paper investigates The Efficiency of E-Recruitment as a New Approach in Selecting Potential Candidate at Technology Park Malaysia Corporation Sdn. Bhd. It consists of investigating of the advantages of using electronic recruitment (online recruitment) that are more relevant nowadays. The first element is to study the present method used which is traditional recruitment process. Second is to investigate the advantages and risk of e-recruitment. Then, I compare the traditional recruitment and e-recruitment process and finds which one is much better. The findings presented will focus on these main issues.